Abusive Supervision and Creativity: Investigating the Moderating Role of Performance Improvement Attribution and the Mediating Role of Psychological Availability - Wang, Can; Wei, Yongchang; Zhao, Xuan; Zhang, Xuan; Peng, Ye (Frontiers in Psychology, 2021)
The existing studies have indicated that abusive supervision affects creativity,however the specific impact mechanism is still unclear due to the uncertain relationship between leadership and employee creativity. Based on resource perspective, this study examines the influence of abusive supervision on creativity through psychological availability (PA) and the moderating of this mediation by performance improvement attribution (PIA). Based on survey of 234 employees, the hypotheses have been tested and the results reveal that abusive supervision had a detrimental effect on employee creativity partially mediated by employee PA, and employees’ PIA moderated the mediation. This study offers new insights into the mechanisms associated with the relationship between abusive supervision and creativity.